Application of Conformable Sumudu Decomposition Method for Solving Conformable Fractional Coupled Burger’s Equation - Hassan Eltayeb; Said Mesloub (Journal of Function Spaces)
The conformable double Sumudu decomposition method (CDSDM) is a combination of decomposition method (DM) and a conformable double Sumudu transform. It is an approximate analytical method, which can be used to solve linear and nonlinear partial differential equations. In this work, one-dimensional conformable functional Burger’s equation has been solved by applying conformable double Sumudu decomposition. Two examples are used to illustrate the method.